Anger magamentent in patients with acute myocardial infarction (MAPAMI): protocol of randomized clinical (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This study aims to describe the protocol of a Randomized Clinical Trial (RCT) (NCT 02868216), controlled, parallel, intention-to-treat, of anger management intervention on the endothelial function of post-infarction patients and low control of this emotion. The intervention consisted of two 40-minute individual meetings with monthly frequency. In the intervention group, semi-structured and focal interviews were carried out based on psychoeducation and cognitive-behavioral techniques. Psychoeducation involved the characterization of anger and its influence on the cardiovascular system and sympathetic activation. Skills training aimed at identifying triggers and warning signs. The “time-out” technique was used to recruit forces to change expression. The anger triad (thought, emotion and action) was worked on in cognitive restructuring to promote adaptive responses and emotion management. In this way, this intervention uses cognitive-behavioral techniques to manage anger and promote the improvement of vascular function in post-infarction patients.
Keywords: clinical trial protocol; anger management therapy; cognitive behavioral techniques; endothelium; myocardial infarction